#1

Hello people, I'm desperate. I've been gone from school for three weeks, and I have a Math test tomorrow. And I've forgotten stuff I need to know, so if someone could tell me how I solve these I'd be glad! I need the way you do it, not just the answers. I work with something called polynom in Swedish, and I have no ****ing clue what its called in English. Basically, there are four solutions for X in this case.

This is what I got: x^4-10x^2+9=0. x^2 is re-written t. So the number we have is:

x^4 - 10t + 9= 0

It has FOUR solutions:

x1:

x2:

x3:

x4:

How do I figure this out? Any help would be greatly appreciated!

I'll probably post more stuff here if I can get help.

-DW

This is what I got: x^4-10x^2+9=0. x^2 is re-written t. So the number we have is:

x^4 - 10t + 9= 0

It has FOUR solutions:

x1:

x2:

x3:

x4:

How do I figure this out? Any help would be greatly appreciated!

I'll probably post more stuff here if I can get help.

-DW

#2

If t = x^2, the new formula is t^2 -10t + 9 = 0. Then just solve the quadratic. And sub t = x^2 in again.

#3

If t = x^2, the new formula is t^2 -10t + 9 = 0. Then just solve the quadratic. And sub t = x^2 in again.

+1

this is all you need to solve this problem, then, if you dont know nothing at all its serious ****, son, the pits not the right place. Get your maths book and revise all you can. Stay calm, never panic! those exercises are easy

#4

*throws up all over maths*

#5

+1

this is all you need to solve this problem, then, if you dont know nothing at all its serious ****, son, the pits not the right place. Get your maths book and revise all you can. Stay calm, never panic! those exercises are easy

Ah, from there I can just use the formula-thingy. Ignore the numbers, I just drew somethign real quick. Please god let it be this one. It looks something like this:

#6

If t = x^2, the new formula is t^2 -10t + 9 = 0. Then just solve the quadratic. And sub t = x^2 in again.

This is correct. This equation factors to (t-9)(t-1)=0, which means t=9,1. Since t=x^2, x=3, -3, 1, -1.

#7

...I think he just wanted a hintThis is correct. This equation factors to (t-9)(t-1)=0, which means t=9,1. Since t=x^2, x=3, -3, 1, -1.

Edit: Demon, revise the formula. It's x=(-b+-(sqrt:(b^2-2ac)))/(2a).

I think....lol.

*Last edited by Wratheh at Feb 27, 2008,*

#8

^^ its b^2 - 4ac in the quadratic formula

#9

1)i cant understand your last post

2) here you are the solution from Krgr

2) here you are the solution from Krgr

#10

Just complete the square. Formula sucks.

#11

the bad thing about this is that after you do the quadratic formula your going to have to answer with polars.

#12

Quadramabatic Thingamabobbers.

#13

^^ its b^2 - 4ac in the quadratic formula

Ah, close though. But seriously, someone's already answered it lol.

#14

This is what I got: x^4-10x^2+9=0. x^2 is re-written t. So the number we have is:

t² - 10t + 9= 0

D = b² - 4AC = 100- 4*1*9 = 64 = 8²

t1 = (-b+D^(1/2))/2A = (10+8)/2 = 9

t2 = (-b-D^(1/2))/2a = (10-8)/2 = 1

=> X1 = 9^(1/2) = 3

X2 = = -3

X3 = 1^(1/2) = 1

X4 = = -1

V=[-3, -1 ,1 ,3]

t² - 10t + 9= 0

D = b² - 4AC = 100- 4*1*9 = 64 = 8²

t1 = (-b+D^(1/2))/2A = (10+8)/2 = 9

**(X^(1/2) = square root of X)**t2 = (-b-D^(1/2))/2a = (10-8)/2 = 1

=> X1 = 9^(1/2) = 3

X2 = = -3

X3 = 1^(1/2) = 1

X4 = = -1

V=[-3, -1 ,1 ,3]

#15

Why would you use the formula.

Just factorize it.

Just factorize it.

#16

Why would you use the formula.

Just factorize it.

It's cause I have a deep sensual passion for formulas.

#17

Pfft, wasn't my reply helpful enough for you? I basically told you all you need to know.

#18

Why not use synthetic division to factorise then do the same for the co-efficient?